PENGEMBANGAN MEDIA PROMOSI KESEHATAN VIDEO MENGENAI KEPATUHAN MINUM OBAT PADA PASIEN HIPERTENSI (Politeknik Kesehatan Kemenkes Bandung, 2021)
One of the treatment processes for hypertensive patients is taking medication for hypertension. Compliance with medication for hypertensive patients aims to reduce the risk of cardiovascular, cerebrovascular and kidney disease, so it is important in the treatment process for hypertensive patients to take medication regularly. The use of video information media is one of the media to improve medication adherence to achieve success in therapy. The purpose of this research is to develop a video health promotion media regarding medication adherence in hypertensive patients. This type of research uses mixed methods with an exploratory sequential mixed methods approach. This research phase begins with the process of exploring the need for video health promotion media with 5 resource persons. Then make a prototype of health promotion media based on 3 stages of the ADDIE development model, namely the analysis, design and development stages. The results of the first stage of the study, namely the validation of material experts, were said to be suitable for use with a value of 72%, the second stage, the value of 86% from the material experts in the very appropriate category, and the third stage of the validation test results by means of small-scale trials with 13 hypertensive patients, the value of 91% was categorized as very proper to use. The conclusion of this study is an animated video regarding adherence to taking hypertension medication in hypertensive patients was developed through 3 stages of ADDIE development, namely analysis, design and development with the results of valid video media validation used.